(untitled) (Journal of Hama University, 2026)
This study aimed to measure the stability of the DWX index for the Damascus Securities Exchange (DSE) for the period 2012-2023. The study then calculated the daily value-at-risk (VaR) on a quarterly basis during the study period, with the aim of measuring the impact of this VaR on the DWX index. This was done using a set of statistical programs: Excel, Eviews 13, and SPSS 2025. The most important findings reached by the researcher were the stability of the DWX series for the Damascus Securities Exchange index at a certain level. This could be attributed to the small number of companies listed on the market and the frequency of stock trading, which leads to stability in the daily index value. The study also found an impact of the VaR of the DSE index on trading value, and the effect was significant and positive. The researcher found a weak correlation, as 25% of trading value could be explained using the VaR of the DSE index.